2008
DOI: 10.1002/path.2363
|View full text |Cite
|
Sign up to set email alerts
|

Infection by Helicobacter pylori expressing the BabA adhesin is influenced by the secretor phenotype

Abstract: Helicobacter pylori (Hp) infects half the world's population and causes diverse gastric lesions, from gastritis to gastric cancer. Our aim was to evaluate the significance of secretor and Lewis status in infection and in vitro adherence by Hp expressing BabA adhesin. We enrolled 304 Hp-infected individuals from Northern Portugal. Gastric biopsies, blood and saliva were collected. Polymerase chain reaction (PCR) and immunofluorescence were used to detect BabA+ Hp in gastric biopsies. In vitro adherence by a Bab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…Labeling with FITC and adhesion assays were performed as previously described [8,10,11]. Evaluation of bacterial binding was estimated by the number of adhered bacteria to superficial foveolar epithelium region under 200× magnification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Labeling with FITC and adhesion assays were performed as previously described [8,10,11]. Evaluation of bacterial binding was estimated by the number of adhered bacteria to superficial foveolar epithelium region under 200× magnification.…”
Section: Methodsmentioning
confidence: 99%
“…The blood group antigen binding adhesin (BabA) recognizes ABO(H)/Lewis b blood group antigens expressed in glycoproteins from the gastro-intestinal tract by secretor individuals [810], whereas the sialic acid binding adhesin (SabA) mediates bacterial attachment through binding to α2,3-sialylated structures, such as sialyl-Lewis a (sialyl-Le a ) and sialyl-Lewis x (sialyl-Le x ) carried by glycosphingolipids and glycoproteins [11]. The babA gene shares regions of high homology with the babB and babC genes.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori BabA binds with Leb and induces the double strand breaks in the host cells, which is thought to be independent of VacA, γ-glutamyl transpeptidase and the cag PAI[94]. However, it has been also confirmed that BabA-positive status of infecting strains is associated with CagA-positive, OipA-positive ( oipA “on”) and vacA s1 genotype for the development of intestinal metaplasia[95]. The infection with BabA-positive strains has been associated with the increased risk for development of peptic ulcer diseases in Western countries[41,96].…”
Section: Literature Searchmentioning
confidence: 99%
“…BabA mediated attachment and development of disease are influenced by host expression of Lewis antigens, which is determined by a number of factors, including ABO blood type and secretor status30313233. The risk of ulcer is increased in individuals with blood group O, and in non-secretor individuals who do not express Le b and ABO antigens on gastric epithelial cells or on mucins3031323334.…”
mentioning
confidence: 99%
“…The risk of ulcer is increased in individuals with blood group O, and in non-secretor individuals who do not express Le b and ABO antigens on gastric epithelial cells or on mucins3031323334. Thus, disease outcome is related to both bacterial expression of the BabA adhesin and to ABO glycosylation on gastric epithelial cells and gastric mucins.…”
mentioning
confidence: 99%